Modified iron oxide nanomaterials: Functionalization and application - Bagheri, S.; Julkapli, N.M. (Elsevier, 2016)
Iron oxide magnetic nanoparticles have aroused the interest of researchers of materials' chemistry due to its exceptional properties such as decent magnetic, electric, catalytic, biocompatibility, and low toxicity. However, these magnetic nanoparticles are predisposed towards aggregation and forming larger particles, due to its strong anisotropic dipolar interactions, particularly in the aqueous phase, consequently depriving them of dispersibility and particular properties, ultimately degrading their performance. Hence, this review focuses on modified magnetic nanoparticles that are stable, easily synthesized, possess a high surface area and could be facile-separated via magnetic forces, and are of low toxicity and costs for applications such as catalyst/catalyst support, food security, biomedical, and pollutant remediation.